Satisfaction of Parents of Musically Gifted Students with the Engagement and Dedication of Teachers and Professional Associates - Nedeljko M. Milanović (Педагогически форум, 2025)
The aim of the research is aimed at assessing the satisfaction of parents of musically gifted students with the engagement and dedication of teachers and professional associates. The sample included 70 parents of musically gifted students. When we look at the calculated mean values for the satisfaction of parents of musically gifted students with the engagement and dedication of teachers and professional associates, we notice that the values calculated for the satisfaction of parents of musically gifted students with the engagement and dedication of professional associates are slightly lower. Parents are not satisfied with the education that teachers and professional associates organize for parents of musically gifted students. Statistically significant differences were found between gender, age, employment status, financial income and satisfaction of parents of musically gifted students with the engagement and commitment of teachers and professional associates.